Loss of Continuity of Care in Pediatric Neurology Services during COVID-19 Lockdown: An Additional Stressor for Parents - Serena Cesario; Consuelo Basile; Matteo Trevisan; Federica Gigliotti; Filippo Manti; Rita Maria Esposito; Giuseppe Abbracciavento; Mario Mastrangelo (MDPI AG, 2022)
Background. This study aimed to investigate the consequence of the COVID 19-related lockdown on the well-being of children with neurological and neurodevelopmental disorders and the repercussion on parental stress during the period 9 March 2020-3 May 2020. Methods. A web-based survey was shared via mail with the parents of children affected by chronic neurologic disorders and neurodevelopmental disorders in the continuity of care in two Italian tertiary centers, independently by the severity of the diseases and the required frequency of controls. For each patient, they were asked to identify a single main caregiver, among the two parents, to fill in the questionnaire. Parental stress was measured via the Perceived Stress Scale (PSS). Statistical analysis was performed with IBM SPSS Statistics version 25. The differences between the clinical groups were performed with one way ANOVA. The dimensional effect of the clinical variables on outcome was evaluated by multiple linear regression analysis. Results. The survey was completed by 250 parents (response rate = 48.9 %). Sars-Cov2 infection was reported in two patients only. A total of 44.2% of the patients had completely interrupted school activities while 70% of parents underwent changes in their job modalities. Health care services were disrupted in 77% of patients. Higher PSS scores were detected in the parents of children with neurodevelopmental disorders (p = 0.035). Conclusions. The loss of continuity of care during the lockdown must be considered as a risk factor for parents caring for children with chronic neurologic diseases and neurodevelopmental disorders in further phases of the current pandemic.